Dehydrogenation Mechanism of Liquid Organic Hydrogen Carriers: Dodecahydro‐N‐ethylcarbazole on Pd(111). Issue 33 (15th July 2013) - Amende, Max; Schernich, Stefan; Sobota, Marek; Nikiforidis, Ioannis; Hieringer, Wolfgang; Assenbaum, Daniel; Gleichweit, Christoph; Drescher, Hans‐Jörg; Papp, Christian; Steinrück, Hans‐Peter; Görling, Andreas; Wasserscheid, Peter; et al.
Abstract Dodecahydro‐N‐ethylcarbazole (H12‐NEC) has been proposed as a potential liquid organic hydrogen carrier (LOHC) for chemical energy storage, as it combines both favourable physicochemical and thermodynamic properties. The design of optimised dehydrogenation catalysts for LOHC technology requires a detailed understanding of the reaction pathways and the microkinetics. Here, we investigate the dehydrogenation mechanism of H12‐NEC on Pd(111) by using a surface‐science approach under ultrahigh vacuum conditions. By combining infrared reflection–absorption spectroscopy, density functional theory calculations and X‐ray photoelectron spectroscopy, surface intermediates and their stability are identified. We show that H12‐NEC adsorbs molecularly up to 173 K. Above this temperature (223 K), activation of CH bonds is observed within the five‐membered ring. Rapid dehydrogenation occurs to octahydro‐N‐ethylcarbazole (H8‐NEC), which is identified as a stable surface intermediate at 223 K. Above 273 K, further dehydrogenation of H8‐NEC proceeds within the six‐membered rings. Starting from clean Pd(111), CN bond scission, an undesired side reaction, is observed above 350 K. By complementing surface spectroscopy, we present a temperature‐programmed molecular beam experiment, which permits direct observation of dehydrogenation products in the gas phase during continuous dosing of the LOHC. We identify H8‐NEC as the main product desorbing from Pd(111). The onset temperature for H8‐NEC desorption is 330 K, the maximum reaction rate is reached around 550 K. The fact that preferential desorption of H8‐NEC is observed even above the temperature threshold for H8‐NEC dehydrogenation on the clean surface is attributed to the presence of surface dehydrogenation and decomposition products during continuous reactant exposure.